Numerical study of delamination process of the CFRP composite - Eva Kormanikova; Kamila Kotrasova (Fracture and Structural Integrity)
A quasi-static approach for an interface damage model, incorporating Rayleigh damping for viscoelastic carbon fiber reinforced polymer composites, is introduced. The interface traction-relative displacement behavior is modeled using a thin adhesive layer, similar to cohesive zone models. The problem is solved numerically with a semi-implicit time-stepping method. The cohesive interface model, integrated into the Finite Element Method, was applied to determine the critical force away from the crack tip. Results showed that the numerical delamination under mode I conditions aligned well with experimental data for the cohesive zone formulations studied. The numerical example demonstrates the effectiveness of the proposed model